A permanent N2O sink in the Nordic Seas and its strength and possible variability over the past four decades. Issue 8 (6th August 2016) - Zhan, Liyang; Chen, Liqi; Zhang, Jiexia; Yan, Jinpei; Li, Yuhong; Wu, Man
Abstract: Nordic Seas have been assumed to be a net sink of the ozone‐depleting greenhouse gas N2 O. However, few studies have been conducted in this region. N2 O profile data obtained during the 5th Chinese National Arctic Research Expedition demonstrate that the N2 O distribution pattern in the Nordic Seas differs from that of most other oceans. N2 O sink characteristics of this region are confirmed by the undersaturation of N2 O in the water column. Distributions of N2 O in three subbasins of the Nordic Seas vary in the upper 1000 m but are homogenous below 1000 m due to a shared origin in the Greenland Basin (GB). Air‐sea exchange and vertical convection are thought to be dominant factors in N2 O distribution in the GB, resulting in a distribution pattern that correlates significantly with the atmospheric mixing ratio variation over the past 40 years. Although recent studies have shown that weakened convection and/or enhanced Arctic outflow below the mid‐depth have occurred, our results show that these variations have yet to significantly affect the above relationship. The distribution could be considered a "historical record" that can be used to evaluate the air‐to‐sea flux over the past 40 years in the GB. The annual amount of N2 O absorbed by the GB is ∼0.016–0.029 Tg N, which is equal to 0.4–0.8% of the world ocean emissions. This amount should not be simply neglected because it is absorbed by a region that accounts for only 0.03% of the world ocean area. Key Points: N2 O in the Nordic Seas is hydrographic dominated Greenland Sea is a permanent sink for N2 O Sink strength over the past 40 year is evaluated